2019
DOI: 10.1017/ice.2019.161
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ultraviolet light surface decontamination in hospital rooms: A primer

Abstract: Ongoing challenges in maintaining optimum manual cleaning and disinfection of hospital rooms have created increased interest in “no-touch” decontamination technologies including the use of ultraviolet light (UV). Trials have shown that some UV devices can decrease surface contamination and reduce healthcare-associated infections. Despite substantial marketing of these devices for use in healthcare settings, few data are available regarding the doses of UV-C necessary to yield desired reductions in healthcare p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 45 publications
5
58
0
4
Order By: Relevance
“…Second, we applied the test organisms in a liquid suspension directly onto the surface of the N95 respirators and spread them over a relatively small surface area with a loop. We cannot exclude the possibility that the technologies would have been more effective if the inoculum was spread out over a larger surface area; spreading of an organism inoculum over a larger surface area has been shown to increase the efficacy of UV-C light [14][15]. It has also been suggested that the method of deposition may influence results, and that methods that more closely mimic droplet and aerosol deposition on respirators should be used [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we applied the test organisms in a liquid suspension directly onto the surface of the N95 respirators and spread them over a relatively small surface area with a loop. We cannot exclude the possibility that the technologies would have been more effective if the inoculum was spread out over a larger surface area; spreading of an organism inoculum over a larger surface area has been shown to increase the efficacy of UV-C light [14][15]. It has also been suggested that the method of deposition may influence results, and that methods that more closely mimic droplet and aerosol deposition on respirators should be used [6].…”
Section: Discussionmentioning
confidence: 99%
“…The high-level disinfection cabinet generates submicron droplets of aerosolized peracetic acid and hydrogen peroxide and has been shown to be very effective in eliminating microorganisms from hard surfaces in patient rooms and on portable equipment [12][13]. We hypothesized that the disinfection cabinet would be very effective while UV-C light might have reduced efficacy in contrast to previous reports that evaluated microorganism reductions on steel disk carriers or hard surfaces in healthcare settings [14][15]. Soft, irregular surfaces may present a challenge for UV-C decontamination due to the potential for areas of shadowing and absorption of organisms into sites with reduced delivery of UV-C [16].…”
Section: Introductionmentioning
confidence: 95%
“…In conclusion, UV-C disinfection can be efficacious in hyperbaric chambers by reducing the levels of clinically relevant bacteria by at least 3 log 10 , but individual UV-C devices should be tested and optimized internally while also recognizing that similar efficacy may not be achieved with certain pathogens such as C. difficile. 2…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported doses of UVC that yield 3 log 10 reductions of specific pathogens using low-pressure mercury lamps UVC devices, data regarding spectrophotometrically determined doses of 200–320 nm light emitted by pulsed xenon lamps are lacking [21].…”
Section: Introductionmentioning
confidence: 99%